EDUKASI GANGGUAN SARAF TEPI AKIBAT OBAT KEMOTERAPI PADA PASIEN POLI ONKOLOGI RUMAH SAKIT UMUM DAERAH (RSUD) PROVINSI NUSA TENGGARA BARAT - Hunaifi, Ilsa; Briliansy, Briliansy; Anggoro, Joko; Bharata, Irsyadina Hasana; Adhima, Daffa Aulia Faza; Karima, Khaula; Kuta, Putu Cicilia Rarasati; Fitroningtyas, Elvika Aulia; Hidayati, Eriska; Moestafa, Rizka Febriya; Maharani, Baiq Nadya Putri (Jurnal Abdi Insani, 2024)
Peripheral neuropathy is a disorder of peripheral nerve fibres secondary to various pathological processes such as diabetes mellitus, vitamin deficiencies or drugs such as chemotherapy regimen. Clinical symptoms include motor, sensory and autonomic disorders. Cancer patients undergoing chemotherapy are susceptible to experiencing symptoms of peripheral neuropathy caused by anatomical changes (such as distal axonal degeneration) or physiological changes. So, the education of regarding peripheral neuropathy is needed in patients with chemotherapy. This community service activity was conducted in the Oncology Building at West Nusa Tenggara Province General Hospital. Implementing activities regarding education on peripheral nerve disorders due to chemotherapy drugs is carried out by providing pretests, educational materials, post-tests and discussions. In the pretest activity, many participants were still unaware of peripheral nerve disorders due to chemoteraphy side effects. In the post-test, the knowledge score was above average (100%) regarding peripheral nerve disorders due to chemoterapy side effects. This shows an increase in the understanding of the side effects of chemotherapy in oncology outpatients clinic at West Nusa Tenggara Province General Hospital